Imaging characteristics of nontuberculous mycobacterial pulmonary nodules - Nishino Kengo; Iguchi Kesato; Ishibashi Osamu; Sasatani Yuika; Ohara Gen; Kagohashi Katsunori; Satoh Hiroaki (Sciendo, 2021)
Introduction. Nontuberculous mycobacteriosis (NTM) of the lungs can develop nodules. In order to clarify some of the characteristics of lung NTM nodules, we examined volume doubling time (VDT) and maximum standardized uptake value (SUVmax) in positron emission tomography (PET) of pathologically diagnosed NTM nodules.